Understanding of Resilience of Older Adults in Hong Kong: A Qualitative Investigation - Hu, Chun (Gerontol Geriatr Med, 2020)
Purpose: Resilience is an important trait for older adults facing adversity. This qualitative study aimed to identify the characteristics that contribute to resilience in a group of community-dwelling older adults in Hong Kong. Methods: Twenty-five Chinese older adults were invited. Interviews were conducted to collect information about the adverse events in their lives, their attitudes towards adversity and the beliefs underlying their approaches to overcoming adversity. The transcripts were analyzed using qualitative content analysis. Results: Seven themes emerged from the interviews: equanimity, positive attitudes towards life; meaningfulness, self-reliance, social support, environmental support, and spirituality and faith. Conclusion: Our qualitative analysis found that resilience among older adults in Hong Kong is characterized by internal, external and existential factors. The results may be useful for the development of proactive interventions aimed at assisting older adults to enhance the positive experiences in their lives.